Temporal stability of a-Si:H and a-SiNx:H on crystalline silicon wafers. (September 2017) - Cheng, Xuemei; Marstein, Erik Stensrud; You, Chang Chuan; Haug, Halvard; Sabatino, Marisa Di
Abstract: The temporal stability of single layer thin films of hydrogenated amorphous silicon (a-Si:H) and silicon nitride (a-SiNx :H) passivated crystalline silicon wafers have been investigated over 18 months. The thin films were deposited at low temperature with plasma-enhanced chemical vapor deposition (PECVD) onto different substrates, including float zone (FZ) p-type and Czochralski (CZ) n-type silicon. For a-SiNx :H, we investigate the temporal stability dependence on the flow rate of silane (SiH4 ) used during deposition. This was varied from 13 sccm to 50 sccm. The thickness of the a-Si:H and a-SiNx :H thin films was characterized by spectroscopic ellipsometry (SE), whereas the minority carrier effective lifetime (τeff ) and the uniformity of the wafer were measured through carrier density imaging (CDI). We found that for both p-type FZ and n-type CZ silicon substrates, the a-Si:H passivation performance degrades after 150 h and reached a minimum value around 350 h, whereafter the lifetime recovered to a level of 1.1 ms (-16% compare to the initial state) and 1.6 ms (-4%), respectively. Similar trends were also seen on a-SiNx :H passivated samples, but the lowest value was reached after around 550 h. For both p- and n-type substrates passivated by a-SiNx :H passivation, as the flow rate of SiH4 increased, the temporal stability of passivated samples enhanced.